Acquisition of aseptic techniques using virtual reality: a randomized trial on performance, emotion and experience - Chau Ling, Tham; Cheng Wei, Lim; Kong Yen, Liew; Sie Hui, Lim; Manraj Singh, Cheema; Puteri Suhaiza, Sulaiman; Hanis Hazeera, Harith; Hasni Idayu, Saidi (Springer, 2024)
The aseptic technique is essential for minimizing contamination in cell and tissue culture. However, biomedical science undergraduates in Universiti Putra Malaysia face challenges in acquiring hands-on learning experience on proper aseptic techniques due to inadequate facilities, which decreases learning interest and efficiency. To address this, an in-house virtual reality (VR) mobile application, AsepticTech VR, was developed to simulate a cell and tissue culture facility for practicing aseptic techniques. This study aims to investigate the efficacy of AsepticTech VR as a teaching and learning tool. Forty-one biomedical undergraduates were randomly assigned into test and control groups. Both groups attended a pre-test to evaluate the pre-intervention learning performances. Then, only test group participants were given access to AsepticTech VR, while both groups attended traditional lectures and practical sessions for a week. After one week, all participants took a post-test to evaluate their post-intervention learning performances. Additionally, test group participants also completed the modified Differential Emotions Scale (mDES) questionnaire to assess their emotions associated with using AsepticTech VR, and Web-Based Learning Tool (WBLT) questionnaire to assess their learning experience. The results showed that the test group participants had better learning performance improvements in the cognitive (p<0.05) and psychomotor domain (p<0.01) compared to the control group but did not differ in their affective domain. Moreover, the test group demonstrated stronger positive emotions compared to negative emotions (p<0.001) and had positive learning experience with AsepticTech VR. This indicates that AsepticTech VR is an effective teaching and learning tool for cell and tissue culture aseptic techniques.